Implementasi Teori Operant Conditioning Melalui Game Interaktif Kahoot dalam Pelajaran PAI di Sekolah Dasar translate ke bahasa inggris - Alandika, Ozy Vebry; Sutarto, Sutarto; Taqiyuddin, Muhammad (Neolectura, 2024)
An Islamic Education teacher needs to support the implementation of a contemporary learning concept by providing facilities and learning media that can meet students' learning needs. The purpose of this study is to describe the implementation of Operant Conditioning theory through Kahoot interactive game in PAI Lesson at SD Negeri 08 Tebat Karai. This research is based on descriptive qualitative approach using case study method. The research location is SD Negeri 08 Tebat Karai, Kepahiang Regency, Bengkulu. Data were collected using observation, interview, and documentation techniques. The data analysis technique of this research uses the Miles et al approach which consists of three stages, namely data reduction, data presentation, and conclusion drawing. The implementation of Operant Conditioning theory through Kahoot interactive games in PAI lessons at SD Negeri 08 Tebat Karai starts from the preparation of learning designs and teaching materials that meet the needs of students. In the learning process, PAI teachers gradually provide positive reinforcement, negative reinforcement, perform response shaping and extinction steps in order to get the expected behavior change.The results of the implementation of this theory through Kahoot interactive games are that students are more enthusiastic in learning, more motivated, grow confidence and desire to be actively involved, and learning becomes more fun.